Seasonally transported aerosol layers over southeast Atlantic are closer to underlying clouds than previously reported. Issue 11 (12th June 2017) - Rajapakshe, Chamara; Zhang, Zhibo; Yorks, John E.; Yu, Hongbin; Tan, Qian; Meyer, Kerry; Platnick, Steven; Winker, David M.
Abstract: From June to October, low‐level clouds in the southeast (SE) Atlantic often underlie seasonal aerosol layers transported from African continent. Previously, the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) 532 nm lidar observations have been used to estimate the relative vertical location of the above‐cloud aerosols (ACA) to the underlying clouds. Here we show new observations from NASA's Cloud‐Aerosol Transport System (CATS) lidar. Two seasons of CATS 1064 nm observations reveal that the bottom of the ACA layer is much lower than previously estimated based on CALIPSO 532 nm observations. For about 60% of CATS nighttime ACA scenes, the aerosol layer base is within 360 m distance to the top of the underlying cloud. Our results are important for future studies of the microphysical indirect and semidirect effects of ACA in the SE Atlantic region. Key Points: New spaceborne lidar CATS is used to investigate the distance between the smoke layer and underlying clouds in SE Atlantic region Smoke layer is found to be much closer to the underlying clouds than previously expected based on CALIPSO 532 nm observations This suggests a potentially important microphysical indirect effects of smoker aerosols through cloud top entrainment